Організаційно-правові заходи забезпечення прийняття судового рішення в адміністративному судочинстві - Бризгалова, Альона Ігорівна (НУБіП України, 2017)
Дисертація на здобуття наукового ступеня кандидата юридичних наук зі спеціальності 12.00.07 «Адміністративне право і процес; фінансове право; інформаційне право». – Національний університет біоресурсів і природо-користування України, Київ, 2017. Дисертаційне дослідження присвячено з’ясуванню сутності і юридичної природи заходів забезпечення прийняття судових рішень в адміністративному судочинстві України. Для досягнення формування однотипного ставлення науковців та практиків до заходів забезпечення прийняття означених рішень і подальшого спрямування зусиль на їх науково-теоретичне та законодавче вдосконалення, досліджуються поняття «судові рішення», «прийняття судових рішень» та «система заходів забезпечення прийняття судових рішень» відносно адміністративної юстиції. В історичному, термінологічному та теоретико-правовому аспектах розглядаються вказані вище поняття, встановлюється взаємозв’язки та співвідношення таких елементів системи забезпечувальних заходів, як їх організаційно-правові засади, інформаційне, матеріально-технічне (включаючи фінансове), процедурно-управлінське та інші види забезпечення. Аналізується позитивний вплив європейських принципів адміністративного права і процесу, що посилився у зв’язку з активізацією євроінтеграційного процесу в Україні, на вдосконалення законодавчого регулювання, законотворчої та науково-теоретичної діяльності, предметом якої є також і суспільні відносини у публічно-правовій сфері та забезпечення процесу вирішення публічно-правових спорів. Автором визначаються критерії та систематизуються як заходи забезпечення прийняття рішень суддями при здійсненні адміністративного судочинства в Україні, так і окремі елементи системи заходів.
The Dissertation on competition of a Scientific degree of Candidate of Legal Sciences, specialty 12.00.07 Administrative Law and Process; Financial Law; Information Law. – National University of Life and Environmental Sciences of Ukraine. Kyiv, 2017. The dissertation is dedicated to clarifying the essence and the legal nature of the measures of the judicial decision-making at the administrative court of Ukraine. To achieve the formation of the uniform attitude of scholars and practitioners to measures ensuring the adoption of the mentioned decisions and further focus of the efforts on their scientific and theoretical-legal improvements, they study the concept of «court decisions», «court decision-making» and «system of measures to ensure court decision-making» relative to the administrative justice. The chosen theme of the study covers a wide range of issues that are in one way or another connected with the study of historical and theoretical and legal problems of court decisions and their adoption, covering them in the scientific development of specialists of various procedural branches, defining the concepts of «decision-making» and «ensuring decision-making» in the science of management, as well as with the developments of the representatives of administrative-procedural science. The above-mentioned concepts are considered from historical, terminological and theoretical-legal aspects. They establish relationships and correlations of the elements of the system of protective measures as their organizational-legal basis, informational, material and technical (including financial), administrative-procedural and other security. The methodological basis of the dissertation research is a set of general scientific laws and categories of the theory of knowledge, as well as, due to the specific goals and objectives of the study, special-scientific methods. They analyze the positive impact of the European principles of administrative law and procedure, which increased due to the intensification of European integration in Ukraine, on improvement of legal regulation, law-making, scientific and theoretical activity, which subject is public relations in the legal area and ensuring the legal procedure of the public disputes settlement. The author defines criteria and systematizes both measures to ensure the decision-making by judges in the administrative justice in Ukraine, and some elements of the security. The dissertation is performed by the competitor in person and is an independent development on the chosen topic. The main provisions, conclusions and proposals that determine the scientific novelty and are put forward in defense, are individually formulated and grounded by the competitor and reflected in seven scientific works.
Keywords: адміністративне судочинство; судові рішення; прийняття судового рішення; забезпечення прийняття судового рішення; система заходів забезпечення адміністративна юстиція; administrative law; judicial decision-making; judicial decisions; ensuring the judicial decision-making; system of security measures; administrative justice